Current Status of Cardiac Xenotransplantation: Report of a Workshop of the German Heart Transplant Centers, Martinsried, March 3, 2023 - Schmoeckel, Michael; Längin, Matthias; Reichart, Bruno; Abicht, Jan-Michael; Bender, Martin; Michel, Sebastian; Kamla, Christine-Elena; Denner, Joachim; Tönjes, Ralf Reinhard; Schwinzer, Reinhard; Marckmann, Georg; Wolf, Eckhard; Brenner, Paolo; Hagl, Christian (The Thoracic and Cardiovascular Surgeon, 2024)
This report comprises the contents of the presentations and following discussions of a workshop of the German Heart Transplant Centers in Martinsried, Germany on cardiac xenotransplantation. The production and current availability of genetically modified donor pigs, preservation techniques during organ harvesting, and immunosuppressive regimens in the recipient are described. Selection criteria for suitable patients and possible solutions to the problem of overgrowth of the xenotransplant are discussed. Obviously microbiological safety for the recipient and close contacts is essential, and ethical considerations to gain public acceptance for clinical applications are addressed. The first clinical trial will be regulated and supervised by the Paul-Ehrlich-Institute as the National Competent Authority for Germany, and the German Heart Transplant Centers agreed to cooperatively select the first patients for cardiac xenotransplantation.
Keywords: xenotransplantation; preclinical; clinical; cardiac